Prognostic impact of early minimal residual disease combined with complete molecular evaluation in acute myeloid leukemia with mutated NPM1: a single center study. Issue 9 (29th July 2022) - Memoli, Mara; Genthon, Alexis; Favale, Fabrizia; Lapusan, Simona; Johnson, Natacha; Adaeva, Rosa; Deswarte, Caroline; Battipaglia, Giorgia; Malard, Florent; Duléry, Rémy; Brissot, Eolia; Banet, Anne; et al.
Abstract: We evaluated prognostic factors in 83 intensively treated adult patients with NPM1 mutated AML. Targeted next-generation sequencing revealed high frequency of co-mutations in epigenetic modifiers or proliferation pathways. NPM1 minimal residual disease (MRD), assessed in bone marrow by specific polymerase chain reaction after one chemotherapy course, was >0.01% in 50 patients considered poor responders (PR). On multivariate analysis, including all variables with a p value <.1 on univariate analysis, age >60, performance status (PS) ≥1, presence of FLT3 mutations, DNMT3A -R882, and PR status, were independently associated with lower leukemia-free survival. Age >60, a previous hematological disease and PR status were independent negative predictive factors for overall survival. In our study, early NPM1 MRD was confirmed as an important prognostic factor. All FLT3 and DNMT3A -R882 mutations have also an independent prognostic value. We support the rational for in-depth investigations for a better approach in patients who achieving a first complete remission.